2021
DOI: 10.3389/fpsyt.2021.684445
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Plasma Antioxidants in Behavioral Symptoms of Individuals With Autism Spectrum Disorder

Abstract: The balance between antioxidant capacity and oxidative stress-induced free radicals may be crucial in the pathophysiological development factor of autism spectrum disorder (ASD). We measured the following urinary and plasma biomarker levels of oxidative stress and antioxidants. As urinary biomarkers, (1) hexanoyl-lysine (HEL), which is a new biomarker of oxidative stress, (2) the total antioxidant capacity (TAC), and (3) 8-hydroxy-2′-deoxyguanosine (8-OHdG), as a product of oxidative modifications to DNA; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
0
1
0
Order By: Relevance
“…This finding is in agreement with previously published enhanced circulating CAT activities in ASD patients [33], although a decrease in the activity of circulating SOD was reported in these patients as well, consistently with recently published data [41]. Although we did not notice modifications in SOD activity in ASD patients, either in the blood plasma or in the RBCs, our experiments support other observations also reporting no changes in SOD activity, either in the RBCs or in the plasma of ASD individuals [19,42,43]. In contrast, SOD activity in the RBCs of ASD patients has been found to be higher [34,39,40,44] as well as lower [45] compared with neurotypical individuals.…”
Section: Changes In Oxidative Stress Markers In Children With Asdsupporting
confidence: 94%
“…This finding is in agreement with previously published enhanced circulating CAT activities in ASD patients [33], although a decrease in the activity of circulating SOD was reported in these patients as well, consistently with recently published data [41]. Although we did not notice modifications in SOD activity in ASD patients, either in the blood plasma or in the RBCs, our experiments support other observations also reporting no changes in SOD activity, either in the RBCs or in the plasma of ASD individuals [19,42,43]. In contrast, SOD activity in the RBCs of ASD patients has been found to be higher [34,39,40,44] as well as lower [45] compared with neurotypical individuals.…”
Section: Changes In Oxidative Stress Markers In Children With Asdsupporting
confidence: 94%
“…However, in general, authors discuss the benefits of antioxidant therapy for the correction of cognitive functions [25][26][27]. Oxidative stress plays an undeniable role in the pathogenesis of ASD [28][29][30][31]. The beneficial effects of antioxidants on ASD symptoms have been noted in many studies [32], especially for antioxidants with anti-inflammatory properties [33].…”
Section: Introductionmentioning
confidence: 99%
“…ROS and RNS are products of cellular metabolism and primarily, they include superoxide radical (O 2− ), nitric oxide radical, hydroxyl radical, hydrogen peroxide (H 2 O 2 ), and peroxynitrite radicals [ 36 , 37 ]. Postmortem brain tissues, urine, plasma, and serum samples from ASD individuals show markers for the production of ROS and RNS as well as impaired glutathione activity, which provides protection against oxidative stress [ 33 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the genetically modified mouse models, which have a similar oxidant-antioxidant profile to individuals with ASD, it is also shown that a decrease in the glutathione causes an increase in repetitive autism-like behaviors [ 44 ].…”
Section: Introductionmentioning
confidence: 99%